Hadith #2372 - Sunan Abi Dawud - Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) had himself cupped when he was fasting. Abu Dawud said: Wuhaib b. Khalid narrated a similar tradition from Ayyub through a different chain of narrators. Ja’far b. Rabi’ah and Hisham, that is, Ibn Hassan, narrated a similar tradition from ‘Ikrimah on the authority of Ibn ‘Abbas.
Grade: Sahih

Hadith #2455 - Sunan Abi Dawud - Abdullah ibn al-Harith ibn Nawfal; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Umm Hani bint Abi Talib; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
When the Prophet (ﷺ) entered upon me, he would ask: Do you have food ? When we said: No, he would say: I am fasting. Waki’ added in his version: Another day when he entered upon us, we said: Messenger of Allah, some pudding (hair) has been presented to us and we have retained it for you. He said: Bring it to me. Talhah said: He fasted in the morning, but broke his fast (that day).
Grade: Sahih

Hadith #2646 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ibn ‘Abbas said “When the verse “If there are twenty amongst you patient and persevering, they will vanquish two hundred” was revealed. It was heavy and troublesome for Muslims when Allaah prescribed for them that one (fighting Muslim) should not fly from ten (fighting Non-Muslims). Then a light commandment was revealed saying “For the present Allaah hath lightened your (task).” The narrator Abu Tawbah recited the verse to “they will vanquish two hundred.” When Allaah lightened t
Grade: Sahih

Hadith #3152 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Ahmad bin Hanbal أحمد بن حنبل; ibn Abbas; Maqsim bin Bajra مقسم بن بجرة; Uthman bin Muhammad; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
“of cotton”. The narrator said: Aisha was told that the people said that he was shrouded in two garments and one cloak. She replied: A cloak was brought but they returned it and did not shroud him in it.
Grade: Sahih

Hadith #4597 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mujahid bin Jabir مجاهد بن جبر; Yazid bin Abi Ziyad يزيد بن أبي زياد (Sunan Abi Dawud)
Mu`awiyah b. Abi Sufiyan stood among us and said: Beware! The Apostle of Allah (ﷺ) stood among us and said: Beware! The people of the Book before were split up into seventy two sects, and this community will be split into seventy three: seventy two of them will go to Hell and one of them will go to Paradise, and it is the majority group. Ibn Yahya and `Amr added in their version : “ There will appear among my community people who will be dominated by desires like rabies which penetrates its
Grade: Hasan

Hadith #5221 - Sunan Abi Dawud - Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; ibn Umar; Yazid bin Abi Ziyad يزيد بن أبي زياد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Ilyas ibn Dighfal said: I saw AbuNadrah kissing on the cheek of al-Hasan.
Grade: Sahih